Interleukin 1 Receptor 1 Knockout and Maternal High Fat Diet Exposure Induces Sex-Specific Effects on Adipose Tissue Adipogenic and Inflammatory Gene Expression in Adult Mouse Offspring - Bridge-Comer, Pania E.; Plows, Jasmine F.; Ramzan, Farha; Patel, Rachna; Ganapathy, Thashma P.; Stanley, Joanna L.; Vickers, Mark H.; Reynolds, Clare M. (Frontiers in Physiology, 2020)
Background: The global incidence of obesity continues to rise, increasing the prevalence of metabolic diseases such as insulin resistance, dyslipidemia, and type 2 diabetes mellitus. Low-grade chronic inflammation, associated with the obese state, also contributes to the development of these metabolic comorbidities. Interleukin-1-receptor-1 (IL-1R1), a pro-inflammatory mediator, bridges the metabolic and inflammatory systems. In young male mice, deficiency of IL-1R1 (IL-1R1-/-) paired with a high-fat diet (HFD) offered beneficial metabolic effects, however in female mice the same pairing led to metabolic dysfunction. Therefore, we examined the contribution of maternal HFD in combination with IL1R1-/- to metabolic health in adult offspring. Methods: Female C57BL/6 and IL-1R1-/- mice were randomly assigned to a control diet (10% kcal from fat) or HFD (45% kcal from fat) 10 days prior to mating and throughout gestation and lactation. Male and female offspring were housed in same-sex pairs post-weaning and maintained on control diets until 16 weeks old. At 15 weeks an oral glucose tolerance test (OGTT) was performed to assess glucose tolerance. Histological analysis was carried out to assess adipocyte size and gene expression of adipogenic and inflammatory markers were examined. Results: IL-1R1-/- contributed to increased body weight in male and female adult offspring, irrespective of maternal diet. IL-1R1-/- and maternal HFD increased adipocyte size in the gonadal fat depot of female, but not male offspring. In female offspring there was reduced expression of genes involved in adipogenesis and lipid metabolism in response to IL1R1-/- and maternal HFD. While there was an increase in inflammatory gene expression in response to maternal HFD, this appeared to be reversed in IL1R1-/- female offspring. In male offspring there was no significant impact on adipogenic or lipid metabolism pathways. There was an increase in inflammatory gene expression in IL1R1-/- male offspring from HFD-fed mothers. Conclusion: This study suggests that IL-1R1 plays a complex and important role in the metabolic health of offspring, impacting adipogenesis, lipogenesis and inflammation in a sex-specific manner.